Reparation by Hard Facing of the Damaged Secondary Stone Crushers - Lazic, Vukic; Arsic, Dusan; Nikolic, Ruzica; Mutavdzic, Milan; Mesko, Jozef (Manufacturing Technology Journal, 2016)
The possibilities for reparation by hard facing of the damaged working parts - the hammers of the secondary stones crusher are investigated in this paper. The analyzed crusher is stationary and it belongs into a group of the process equipment aimed for producing the crushed stone. The produced stone is later used for manufacturing various construction materials like asphalt, concrete, etc. Wear of the crusher's working parts occurs during the exploitation due to operation with very hard materials. That wear is usually abrasive and of high intensity what causes failure of the working parts and consequently the machine's downtimes and appearance of various types of losses, primarily financial ones. To prevent that, and to reduce the downtimes as well, one uses reparation technologies, one of which is hard facing. The analysis of the mass losses of the hard faced parts, after certain number of hours of the crusher's field operation, is performed in this paper.
Keywords: Reparation; Hard facing; Hammer; Secondary crusher